Measurement of the Electron Charge Asymmetry in p(p)over-bar -> W plus X -> e nu plus X Events at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Mundal, O.; et al. (Amer Physical Soc, 2008)
We present a measurement of the electron charge asymmetry in p (p) over bar -> W + X -> e nu + X events at a center of mass energy of 1.96 TeV using 0.75 fb(-1) of data collected with the D0 detector at the Fermilab Tevatron Collider. The asymmetry is measured as a function of the electron transverse momentum and pseudorapidity in the interval (-3.2, 3.2) and is compared with expectations from next-to-leading order calculations in perturbative quantum chromodynamics. These measurements will allow more accurate determinations of the proton parton distribution functions.